2020
DOI: 10.3390/plants9060682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and Mineral Nutrition on Growth and Physiological Responses of Trembling Aspen (Populus tremuloides), Jack Pine (Pinus banksiana), and White Spruce (Picea glauca) Seedlings in Sand Culture

Abstract: Responses of trembling aspen (Populus tremuloides), jack pine (Pinus banksiana), and white spruce (Picea glauca) seedlings to root zone pH ranging from 5 to 9 were studied in sand culture in the presence of two mineral nutrition levels. After eight weeks of treatments, effects of pH on plant dry weights varied between the plant species and were relatively minor in white spruce. Higher nutrient supply significantly increased dry weights only in trembling aspen subjected to pH 5 treatment. There was little effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…In this study, as the biochar ratio increased from 25% to 75%, the pH of media increased, which might have caused a decrease in the total dry weight of the plant because of the decreased nutrient uptake (Graber et al 2010). A high pH restricts nutrient uptake by elevating the root apoplastic pH and disturbing the pH gradient between membranes, thus causing a reduction in the nutrient levels of NO 3 , P, and Mg (Xu et al 2020). In addition to a high pH, there are various factors that influence plant growth and development.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, as the biochar ratio increased from 25% to 75%, the pH of media increased, which might have caused a decrease in the total dry weight of the plant because of the decreased nutrient uptake (Graber et al 2010). A high pH restricts nutrient uptake by elevating the root apoplastic pH and disturbing the pH gradient between membranes, thus causing a reduction in the nutrient levels of NO 3 , P, and Mg (Xu et al 2020). In addition to a high pH, there are various factors that influence plant growth and development.…”
Section: Discussionmentioning
confidence: 74%
“…in the soils of these different sites. [25], have also shown that soil pH and hydromineral nutrition significantly influence growth in poplar (Populus tremuloides), jack pine (Pinus banksiana), and white spruce (Picea glauca) seeds grown on sand. According to [26], the nature and properties of the soil play a critical role in plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, the implications of the described responses of the roots for the long-term response of the whole plant should be investigated further. Furthermore, the overall findings from nutrient solution experiment have to be drawn with care to the limitation of such system and in relation to findings from sand and soil systems (Xu et al, 2020). The slightly alkaline pH treatment caused also to deficiency of Mn in the leaves.…”
Section: Discussionmentioning
confidence: 99%